2008
DOI: 10.1063/1.2833957
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods for calculating the paramagnetic relaxation enhancement of nuclear spins as a function of the magnetic field

Abstract: The enhancement of the spin-lattice relaxation rate for nuclear spins in a ligand bound to a paramagnetic metal ion [known as the paramagnetic relaxation enhancement (PRE)] arises primarily through the dipole-dipole (DD) interaction between the nuclear spins and the electron spins. In solution, the DD interaction is modulated mostly by reorientation of the nuclear spin-electron spin axis and by electron spin relaxation. Calculations of the PRE are in general complicated, mainly because the electron spin intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
120
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 58 publications
3
120
0
Order By: Relevance
“…Several experimental studies of 1 H NMRD profiles obtained for different paramagnetic systems have been reported [12]- [15], and various computational methods have been developed to describe these systems [16]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies of 1 H NMRD profiles obtained for different paramagnetic systems have been reported [12]- [15], and various computational methods have been developed to describe these systems [16]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…While the molecular factors influencing (1) and (2) are rather well understood [2][3][4][5] , the electronic spin relaxation of Gd(III) complexes relevant for MRI remains the subject of much discussion [6][7][8][9][10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…The three NMRD models compared above 33 are based on the same description of the ZFS interactions. The ZFS coupling is split into a permanent (static) part modulated by the molecular tumbling and a fluctuating (transient) part varying in time mostly by the distortional (vibrational) motion of the complex.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, one should mention somewhat different implementations of the slow motion theory, SLE-L, (stochastic Liouville equation in Langevin form) presented by Åman and Westlund. 31,32 Predictions of the slow motion theory 30 were recently compared 33 with two other treatments, referred to as the Grenoble, 21,34 and Ann Arbor approaches, [35][36][37] respectively. It was found that the "Swedish slow motion theory" and the Grenoble approach agreed very well with each other, while some discrepancies were observed when compared to the Ann Arbor method, which was explained by a somewhat different description of the electron spin dynamics.…”
Section: Introductionmentioning
confidence: 99%